Severe visceral leishmaniasis in children: the relationship between cytokine patterns and clinical features - GAMA, Mônica Elinor Alves (Universidade Federal do Pará, 2017)
Introduction: The relationship between severe clinical manifestations of visceral leishmaniasis (VL) and immune response profi les has not yet been clarifi ed, despite numerous studies on the subject. This study aimed to investigate the relationship between cytokine profi les and the presence of immunological markers associated with clinical manifestations and, particularly, signs of severity, as defi ned in a protocol drafted by the Ministry of Health (Brazil). Methods: We conducted a prospective, descriptive study between May 2008 and December 2009. This study was based on an assessment of all pediatric patients with VL who were observed in a reference hospital in Maranhão. Results: Among 27 children, 55.5% presented with more than one sign of severity or warning sign. Patients without signs of severity or warning signs and patients with only one warning sign had the highest interferon-gamma (IFN-γ) levels, although their interleukin 10 (IL-10) levels were also elevated. In contrast, patients with the features of severe disease had the lowest IFN-γ levels. Three patients who presented with more than two signs of severe disease died; these patients had undetectable interleukin 2 (IL-2) and IFN-γ levels and low IL-10 levels, which varied between 0 and 36.8pg/mL. Conclusions: Our results showed that disease severity was associated with low IFN-γ levels and elevated IL-10 levels. However, further studies with larger samples are needed to better characterize the relationship between disease severity and cytokine levels, with the aim of identifying immunological markers of active-disease severity.